Dopaminergic Dysregulation in Prefrontal Cortex of Rhesus Monkeys Following Cocaine Self-Administration - McIntosh, Scot; Howell, Leonard H.; Hemby, Scott E. (Frontiers in Psychiatry, 2013)
Chronic cocaine administration regulates the expression of several proteins related to dopaminergic signaling and synaptic function in the mesocorticolimbic pathway, including the prefrontal cortex. Functional abnormalities in the prefrontal cortex are hypothesized to be due in part to the expression of proteins involved in dopamine signaling and plasticity. Adult male rhesus monkeys self-administered cocaine (i.v.) under limited (n=4) and extended access conditions (n=6). The abundance of surrogate markers of dopamine signaling and plasticity in the dorsolateral prefrontal cortex (DLPFC), orbitofrontal cortex (OFC) and anterior cingulate cortex (ACC) were examined: glycosylated and non-glycosylated forms of the dopamine transporter (efficiency of dopamine transport), tyrosine hydroxylase (TH; marker of dopamine synthesis) and phosphorylated TH at Serine 30 and 40 (markers of enzyme activity), extracellular signal-regulated kinase 1 and 2 (ERK1 and ERK 2) and phosphorylated ERK1 and ERK2 (phosphorylates TH Serine 31; markers of synaptic plasticity), and markers of synaptic integrity, spinophilin and post-synaptic density protein 95 (roles in dopamine signaling and response to cocaine). Extended cocaine access increased non-glycosylated and glycosylated DAT in DLPFC and OFC. While no differences in TH expression were observed between groups for any of the regions, extended access induced significant elevations in pTHSer31 in all regions. In addition, a slight but significant reduction in phosphorylated pTHSer40 was found in the DLPFC. Phosphorylated ERK2 was increased in all regions; however, pERK1 was decreased in ACC and OFC but increased in DLPFC. PSD-95 was increased in the OFC but not in DLPFC or ACC. Furthermore, extended cocaine self-administration elicited significant increases in spinophilin protein expression in all regions. Results from the study provide insight into the biochemical alterations occurring in primate prefrontal cortex.